Economic specification of neoclassical production function - case study - Ross, M (Economic & Social Studies, 1971)
A production function may be defined as the mathematical expression of the technological information which relates the quantities of inputs to quantities of outputs. As such, the concept is perfectly general and a specific function may be given as a single point, a set of points, a single continuous or discontinuous function, or a system of equations. The neoclassical production function is essentially a single continuous function with continuous first and second order partial derivatives or a system of such equations. Addressing itself directly to marginal analysis and the neoclassical function this paper excludes consideration of other functions of major importance in economic analysis. Foremost among these are the linear and point functions which underlie most of the studies involving linear programming and game theory and the fixed proportions functions used in Input- Output analysis.
Keywords: Economics